2013
DOI: 10.1186/1749-8090-8-49
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vasopressin on the hemodynamics in CABG patients

Abstract: BackgroundVasopressin is widely used to treat various type of hypotension, but the effect of vasopressin on coronary artery bypass grafting surgery (CABG) patients is not clear. This study was to investigate the effect of vasopressin on the hemodynamics in CABG patients.MethodsTwenty coronary artery disease (CAD) patients were randomly divided into two groups: norepinephrine group and vasopressin group. During the anesthesia and the operation, the central venous pressure (CVP) and pulmonary capillary wedge pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…In vitro and in vivo studies have demonstrated that AVP produces systemic vasoconstriction with relatively fewer effects on the pulmonary circulation; such combined effects produce a desirable decrease in the pulmonary vascular resistance/systemic vascular resistance ratio [ 12 14 ]. This AVP-mediated selective vasoconstriction of the systemic vessels has also been shown in several clinical studies in patients undergoing cardiac surgery [ 4 6 ]. However, the pathological mechanisms of PH in patients who undergo cardiac surgery are different from those in patients with PH secondary to lung diseases.…”
Section: Case Presentationsupporting
confidence: 60%
See 1 more Smart Citation
“…In vitro and in vivo studies have demonstrated that AVP produces systemic vasoconstriction with relatively fewer effects on the pulmonary circulation; such combined effects produce a desirable decrease in the pulmonary vascular resistance/systemic vascular resistance ratio [ 12 14 ]. This AVP-mediated selective vasoconstriction of the systemic vessels has also been shown in several clinical studies in patients undergoing cardiac surgery [ 4 6 ]. However, the pathological mechanisms of PH in patients who undergo cardiac surgery are different from those in patients with PH secondary to lung diseases.…”
Section: Case Presentationsupporting
confidence: 60%
“…Surgery and anesthesia pose a significant risk for patients with pulmonary hypertension (PH) [ 1 3 ]; therefore, perioperative management of these patients presents a major challenge to physicians. Several studies in patients undergoing cardiac surgery have demonstrated that arginine vasopressin (AVP) can effectively ameliorate systemic hypotension without increasing pulmonary vascular resistance [ 4 6 ]. These results support the administration of AVP for the treatment of hypotension concomitant with PH in the cardiac surgery setting.…”
Section: Introductionmentioning
confidence: 99%
“…Yimin et al studied the differences between NE and AVP monotherapies for hypotension in 20 patients undergoing CABG. There was no significant differences between the two therapies but the pulmonary artery pressures were higher in the norepinephrine group . One of the largest prospective studies to examine this was the VANCS trial, which randomized 330 patients with post‐CPB vasodilatory shock to norepinephrine (10‐60mcg/min) or AVP (0.01‐0.06 U.min).…”
Section: Methodsmentioning
confidence: 99%
“…There was no significant differences between the two therapies but the pulmonary artery pressures were higher in the norepinephrine group. 36 One of the largest prospective studies to examine this was the VANCS trial, which randomized 330 patients with post-CPB vasodilatory shock to norepinephrine (10-60mcg/min) or AVP (0.01-0.06 U.min). The study excluded LVAD and OHT populations.…”
Section: Prohylactic Use Of Avp Is Less Well Established Although Stumentioning
confidence: 99%
“…7 The first reports for AVP use in cardiac surgery, by Argenziano et al 8 & Masetti et al, 9 showed promising results referring to its use for separation from cardiopulmonary bypass. More recently, Elgebaly et al 10 & Yimin et al 11 suggested the beneficial role of vasopressin in supporting circulation after heart operations against various conditions, such as low ejection fraction, extended vasodilatation from ACE inhibitors and long bypass time for complex operations.…”
mentioning
confidence: 99%